Āhāra Vidhi Vidhāna & Chrono - Nutrition: An Integrative Approach to Health through Time-Aligned Dietary Practices - K, Kavya; Puranik, Subramanya; K R, Shruthi; M.K, Veena; Gowda H R, Shashank; A D, Sathisha; K M, Anil Kumar; Kumar B G, Chethan (Journal of Neonatal Surgery, 2025)
Āyurveda, the age old traditional system of medicine, encloses a detailed dietary protocol known as Āhāra Vidhi Vidhāna, emphasising the quantity, quality, timing, and mental state of an individual during food intake. Meanwhile, in present era Chrono-nutrition deals with the study of interaction between meal timing (affecting health & metabolism) and its alignment with the body’s circadian rhythm, has emerged as a pivotal concept in modern nutritional science. This integrated approach bridges relation among Āyurveda principle i.e Āhāra Vidhi Vidhāna with chrono-nutrition, highlighting the commonalities and probability for synergistic health benefits. This alignment of consuming food with biological clocks may offer profound metabolic, digestive, and psychological benefits, making this integrative approach a promising area for future clinical research